ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Khoirunisa Nugraha, Syalwa; Amalia Rismanty, Vidya (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to analyze the potential for bankruptcy or financial distress in food and beverages sub-sector companies with the 2018-2022 research period using the altman z-score method. This research is a quantitative type of research using secondary data, the sample companies used are food and beverages sub-sector companies listed on the Indonesia Stock Exchange in 2018-2022. Based on the existing criteria determined by the author, a total of 4 companies that match the existing criteria or benchmarks and the method of sampling using purposive sampling method. The analysis technique uses the altman z-score method. The results of this study indicate that there are two companies that are in the healthy category and there are two companies that are analyzed equally into the category of bankruptcy or distress in each year of research, namely PT Indofood Sukses Makmur Tbk and PT Tri Banyan Tirta Tbk. Because all the results of the calculation of the two companies in each year produce numbers below the cut off value of 1,81 in accordance with the altman z-score method that applies to both companies experiencing financial distress. And the other two companies, namely PT Akasha Wira International Tbk and PT Mayora Indah Tbk, entered into a healthy condition.